Indonesian Food Trade Policy during COVID-19 - Felippa Amanta; Ira Aprilianti (Center for Indonesian Policy Studies (CIPS), 2020)
Indonesia's food security is getting precarious. As COVID-19 spreads, supply chains are being significantly disrupted and is slowing down Indonesia's agricultural production and distribution. Indonesia's poor are being hit hard and are seeing rising food prices, loss of income and unemployment. CIPS' Indonesian Food Trade Policy during COVID-19 Policy Brief outlines three possible trade policy scenarios and their likely consequences on Indonesia's food prices. It includes four policy recommendations to Indonesian policymakers that aim to ensure Indonesians remain food secure during and beyond COVID-19.
Keywords: 330; covid-19; covid19; coronavirus; pippa; ira; import licensing; spi; McKibbin & Fernando; food prices; Ministry of Trade; Importer Identification Number; Ministry of Foreign Affairs; Dynamic Stochastic General Equilibrium modeling